Gambaran tingkat kepuasan pada lansia pemakai gigi tiruan lengkap (Observasi pada Panti Sasana Tresna Werdha Ria Pembangunan) - Alivia, Danisa; Ayu Ratih Utari Mayun, I Gusti (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Loss of all teeth in the elderly is one of the effects of the aging process. Treatment using complete dentures can be a solution for the elderly to restore aesthetic, phonetic, and masticatory functions. Patient satisfaction is the result of patient evaluation that is formed through emotional responses, such as happiness feelings of pleasure and satisfaction arising from the results of a job. One of the goals in complete denture treatment is the success of the treatment. Success of denture treatment can be judged from patient satisfaction. Aim: To describe the level of satisfaction in the elderly who wear complete dentures. Method: This type of research is descriptive observational with a cross-sectional design. This research was conducted by distributing PDA-ID (Patients Denture Assessment-ID) questionnaires to 22 elderly people at the Sasana Tresna Werdha Ria Pembangunan orphanage. Result: There are 21 respondents out of a total of 22 respondents had a high level of satisfaction with the complete denture used. 1 respondent who has a low level of satisfaction with complete dentures make dentures at a dental handyman. Conclusion: Most of the elderly respondents who use complete dentures at the Sasana Tresna Werdha Ria Pembangunan nursing home have a high level of satisfaction with the complete dentures used.